2023
DOI: 10.1002/jdd.13190
|View full text |Cite
|
Sign up to set email alerts
|

The impact of coronavirus disease 2019 pandemic on dental school assessments – Current status and future perspectives

Abstract: Purpose To evaluate course directors’ feedback on the assessment methods used during the coronavirus disease 2019 (COVID‐19) pandemic and identify effective approaches for future assessments in dental education. Methods Course directors at the US dental schools were surveyed for changes in assessments implemented during the early stages of the pandemic (March–July 2020) using the Qualtrics platform. The survey questions addressed assessment methods utilized in didactic, preclinical, and clinical arenas pre‐COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies have typically assessed students' reported experience with online learning, 12,13,14 educators well-being and experience 15 and the efficiency of online assessment. [16][17][18] Nevertheless, some aspects are underrepresented in current literature, such as the changes in students' perceptions of workload, while other such as the role of engaging students in emergency care are only examined in this study to the best of our knowledge.…”
Section: Ta B L Ementioning
confidence: 99%
“…Studies have typically assessed students' reported experience with online learning, 12,13,14 educators well-being and experience 15 and the efficiency of online assessment. [16][17][18] Nevertheless, some aspects are underrepresented in current literature, such as the changes in students' perceptions of workload, while other such as the role of engaging students in emergency care are only examined in this study to the best of our knowledge.…”
Section: Ta B L Ementioning
confidence: 99%